Handheld Total Chemical and Biological Analysis Systems : Bridging NMR, Digital Microfluidics, and Semiconductors /: Bridging NMR, Digital Microfluidics, and Semiconductors. (2017) - Lei, Ka-Meng; Mak, Pui-In; Law, Man-Kay; Martins, Rui Paulo
No abstract available